Analisis Pemanfaatan Media Sosial Dalam Sports Branding Pada Instagram Klub PSIS Semarang - Madani, Ndaru; Nur Suryanto Gono, Joyo; Lukmantoro, Triyono (Interaksi Online, 2024)
The new media era is characterized by the massive use of social media, especially Instagram. Instagram has become a must for society, both individuals, institutions, and football clubs. PSIS Semarang football club is one of the clubs that uses Instagram as a communication page with a wide audience and the use of branding. In this research, the sports branding carried out by the PSIS Semarang Club through Instagram social media will be studied. This research was conducted with a qualitative method and descriptive approach. The data taken in the research is primary data from the social media manager of the PSIS Semarang Club, PSIS Semarang supporters, and Instagram users in general. The data will be processed until a narrative is obtained from each point of view of sports branding carried out by PSIS Semarang. This research provides the following results: 1. Brand Awareness, PSIS Semarang has received good recognition in the community. 2. Brand Image. PSIS Semarang has built a good image on the Instagram platform. 3. Brand Engagement, PSIS Semarang has built good engagement with the audience on the Instagram platform. 4. Content Strategy. PSIS Semarang Instagram contains good content and implements a good strategy. 5. Fan Relationship Management, PSIS Semarang Instagram has built a good relationship with fans. 6. Brand Equity, PSIS Semarang Instagram has a distinctive and special value as a football club. 7. Competitive Advantage, PSIS Semarang through Instagram offers a speed advantage which is an added value to the content. 8. Consistency, PSIS Semarang consistently carries the characteristic object of Semarang City as a symbol in jersey and Instagram. 9. Storytelling, PSIS builds intimate relationships by presenting player life stories. 10. Innovation, PSIS Semarang always provides innovation in the content presented.